What I wish I'd known about raising a child with autism : a mom and a psychologist offer heartfelt guidance for the first five years - Sheahan, Bobbi; DeOrnellas, Kathy (Arlington, TX : Future Horizons, 2011)
'Bobbi Sheahan, mother of a child with autism, and psychologist Kathy DeOrnellas, Ph.D., did not write this book to lecture you on how to parent your child. Instead, they offer themselves as your scouts in the field, who have valuable information to share--from the moment you realize your kid is different ('My, what a quiet baby you have!'), to the self-righteous moms on the playground, to holding your marriage together in the realm of routines. Throughout the book, Bobbi's heartwarmingly humorous'What I wish I'd Known' sections offer sincere parent-to-parent advice. Shaded sections by Dr. DeOrnalles provide additional information based on her rich professional experience and research, supported with lists of references.'--P. [4] of cover.
Includes bibliographical references (p. 217-227) and index.
Keywords: Autistic disorder -- Psychology